2011
DOI: 10.1155/2011/528628
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite Clay-Based Polyurethane Nanocomposite As Local Triamcinolone Acetonide Delivery System

Abstract: Biodegradable polyurethane was synthesized by preparing aqueous polyurethane dispersion having poly(caprolactone) and poly(ethylene glycol) as soft segments. Montmorillonite particles were delaminated within the waterborne polyurethane to produce a nanocomposite. The triamcinolone acetonide (TA), an important corticoid drug, was dispersed into the nanocomposite followed by a drying step to produce an implantable drug delivery system. Infrared (FTIR) results demonstrated that the original chemical structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…It was observed that approximately 40% of MTX was released from PCL implants in vitro and 95% of drug was delivered by PCL implants in vivo during 18 d. The differences between the physiological environment (in vivo test) and the simulated physiological conditions (in vitro test) explain the lack of correlation between the in vivo and in vitro profile release of MTX from PCL implants (Pinto et al, 2011). Figure 8 shows the cytotoxicity of the solution of PCL implants (without drug) against HeLa cells.…”
Section: In Vivo Release Of Mtx From the Pcl Implantsmentioning
confidence: 99%
“…It was observed that approximately 40% of MTX was released from PCL implants in vitro and 95% of drug was delivered by PCL implants in vivo during 18 d. The differences between the physiological environment (in vivo test) and the simulated physiological conditions (in vitro test) explain the lack of correlation between the in vivo and in vitro profile release of MTX from PCL implants (Pinto et al, 2011). Figure 8 shows the cytotoxicity of the solution of PCL implants (without drug) against HeLa cells.…”
Section: In Vivo Release Of Mtx From the Pcl Implantsmentioning
confidence: 99%
“…Alternatively, the minimum units of clay can also be dispersed into the polymer matrix, with marked increase in interaction between the two, producing a material with different characteristics to the parent constituents (21). These are referred to as intercalated and exfoliated systems, respectively.…”
Section: Clay and Polymer-based Composites Applied As Drug Carriersmentioning
confidence: 99%
“…The main drugs carried in the articles analysed were non-steroidal anti-inflammatory drugs (46.1%) (24,39,40,(66)(67)(68), antimicrobial (25.6%) (21,34,65,69,74) and chemotherapeutic agents (10.3%) (13,14). This distribution can be explained by the adverse events associated with the use of these active principles, whether due to the reduction in gastric protection resulting from prolonged use of the anti-inflammatory drugs and analgesics, or to the intrinsic toxicity of chemotherapeutic agents and some antimicrobials associated with the risk of resistance (75,76).…”
Section: Clay and Polymer-based Composites Applied As Drug Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporaneously, researchers have been interested in the investigation of the intercalation reactions (IRs) that involves kaolinite layered phyllosilicates for the purpose of scientific and technological advancements in the areas of catalysis; water filtration; composites; nanotechnology; controlled released formulations [1,2] such as drug delivery systems (DDSs) and controlled release fertilizers (CRFs) [3][4][5][6][7][8][9][10]. Progressive application of kaolinite in the engineering designs has been practically feasible owing to the fact that kaolinite (which is an inexpensive chemical mineral) can be modified through ion exchange mechanisms by just intercalation of ionic species into the kaolinite interlayer spaces.…”
Section: Introductionmentioning
confidence: 99%